Performance of Aman Rice Varieties Under Different Nutrient Management - Mushtaree, A; Sarkar, MAR; Kabiraj, MS; Sarkar, SK; Rashid, MH; Paul, SK (Bangladesh Agronomy Journal, 2023)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during July to December 2017 to investigate the combined effect of poultry manure with inorganic fertilizers on the yield of BINA developed transplant Aman rice varieties. The experiment comprised three varieties viz. Binadhan-15, Binadhan-16 and Binadhan-17 with five nutrient management viz. Control (no application of manures and fertilizers), 100% recommended dose of inorganic fertilizer (Urea-TSP-MoP-Gypsum-Zinc sulphate @ 150-110-70-60-5 kg ha-1) (RF), Poultry manure @ 5 t ha-1, 75% RF + poultry manure @ 5 t ha-1, 50% RF + poultry manure @ 5 t ha-1. The experiment was laid out in a randomized complete block design with three replications. Number of total tillers hill-1 (13.37), number of effective tillers hill-1 (6.76), grains panicle-1 (107.86 cm), grain yield (6.97 t ha-1), straw yield (8.36 t ha-1), and harvest index (45.47%) were found to be the highest in Binadhan-17 and the highest weight of 1000-grain (27.32 g) was recorded in Binadhan-16. Among the nutrient management, 75% RF + poultry manure @ 5 t ha-1 exhibited its superiority to other treatments in terms of number of total tillers hill-1(11.74), grains panicle-1 (115.26), 1000-grain weight (23.49 g), grain yield (6.57 t ha-1) and harvest index (48.20%). The highest grain yield (7.10 t ha-1) was found in Binadhan-17 with 75% RF + poultry manure @ 5 t ha-1 and the lowest grain yield (5.32 t ha-1) was found in Binadhan-16 with control treatment. From the study, it can be concluded that Binadhan-17 fertilized with 75% recommended dose of inorganic fertilizer + poultry manure @ 5 t ha-1 appears as the promising practice to obtain the highest grain yield. Bangladesh Agron. J. 2022, 25(2): 89-96